P126 - A. Makashov; A. Kozlov (EJC Supplements, 2015)
Earlier we showed that at least some of nucleotide sequences with tumor-specific expression are evolutionary novel (reviewed in [A.P. Kozlov, 2014]). In this paper we performed the study of the relative evolutionary novelty of human oncogenes, all protein-coding genes, genes encoding tumor antigens, tumor suppressors and tumor-associated genes using homology searches in genomes of different taxa in human lineage. Materials and methods: The following databases were used as a source of human genes: oncogenes – COSMIC (574 genes), tumor suppressors – TSGene (636 genes), all tumor-associated genes – allOnco (2116 genes) and NCG (2001 genes), cancer-testis (CT) antigen genes – CTDatabase (276 genes) and all annotated human protein coding genes – Genome assembly GRCh38 (21694 genes). The list of cancer vaccine antigen genes was retrieved from paper of Cheever et al., 2007, where 75 cancer antigens were ranked according to their potential suitability for anticancer vaccines. Some of cancer antigens are non-protein molecules, mutant or fusion-proteins. Thus, we examined the evolutionary novelty of only 58 protein-coding cancer vaccine antigen genes. To analyze the evolutionary novelty of the explored genes the HomoloGene release 68 tool and ProteinHistorian tool were used. The HomoloGene tool searches the orthologs in 11 taxa of the human lineage (Eukaryota, Opisthokonta, Bilateria, Euteleostomi, Tetrapoda, Amniota, Boreoeutheria, Euarchontoglires Catarrhini, Homininae, H.sapiens) and the ProteinHistorian tool searches the orthologs in 16 taxa of the human ligeage (Cellular Organisms, Eukaryota, Opisthokonta, Bilateria, Deuterostomia, Chordata, Euteleostomi, Tetrapoda, Amniota, Mammalia, Theria, Eutheria, Euarchontoglires, Catarrhini, Homininae, H.sapiens). To analyze the statistical significance of data Fisher’s exact test was used. Results: Several curves of taxonomic distribution of orthologs of different classes of human genes have been generated. A set of curves forms a peculiar picture where different curves are organized in a definite order. The curves never intersect after Bilateria. The uppermost position occupies the curve which describes the oncogene orthologs distribution. Right below the oncogene curve, the distribution curve of tumor suppressor genes orthologs taxonomic is located, and the difference between these curves is significant. The distribution curves of other tumor-associated genes orthologs overlap with tumor suppressor curve. The medium position in the whole picture is occupied by the distribution curve of orthologs of all human protein-coding genes. Below this curve the distribution curves of orthologs of different tumor antigens are located. The first below the medium curve is tumor vaccine antigen curve, then CT and CT-X antigen genes orthologs distribution curves are located. Thus at any given timepoint the relative proportion of oncogene orthologs described by distribution curve is higher than of any other studied class of human genes. Conclusion: 1. The evolution of human oncogenome advances ahead of all other human gene classes. 2. On the other hand, the evolution of tumor antigen gene classes goes behind the rest of human gene classes, i.e. tumor antigens genome is more evolutionary novel.